The Papers of Thomas A. Edison Losses and Loyalties, April 1883-December 1884 - Edison, Thomas A. (Johns Hopkins University Press, 2011)
Seeking to replicate the success of his New York electric central station throughout the United States and in Europe and Latin America, Thomas A. Edison vowed to become a "business man for a year." This bold decision began a remarkable transition period for America's greatest inventive thinker. The seventh volume of Edison's papers chronicles the profound changes in his professional and personal life, including the unexpected death of his wife. It concludes with Edison returning to the laboratory to develop new communications technology.